MODEL TEORI KONSEP KEPERAWATAN NOLA J PENDER ‘HEALTH PROMOTION MODEL’ - Euis Purwatyningsih; Irna Nursanti (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
The Health Promotion Model by Nola J. Pender reflects an evolution in nursing approaches, moving beyond a reactive paradigm to a proactive focus on prevention and health promotion. Grounded in a holistic health philosophy, the model recognizes the complexity of interactions between physical, psychological, and social aspects in shaping a person's health. Building on previous theories, the model offers a solid empirical foundation, reinforcing its relevance in various contexts and populations. The model's strength lies in its deep orientation towards prevention, filling a void in nursing practice that previously underemphasized disease prevention efforts. While it empowers individuals to manage their own health, the model may be difficult to apply to individuals with low economic means or mental disabilities. Overall, the Health Promotion Model has been a major contributor in shifting the nursing paradigm towards prevention and health promotion.